Disaster : Hurricane Katrina and the failure of Homeland Security - Cooper, Christopher; Block, Robert (New York : Henry Holt and Co., 2007)
"When Hurricane Katrina roared ashore on August 29, 2005, federal and state oifficials were not prepared for the devestation it would bring. In this seariung indictment of what went wrong, Christopher Cooper and Robert Block of The Wall Street Journal take readers inside FEMA and the Department of Homeland Security to reveal the inexcusable mismanagement during the crisis - the bad decisions that were made, the facts that were ignored, and the individuals who saw the system was broken but did nothing to fix it.
"In this award winning and critically acclaimed book, Cooper and Block reconstruct the crucial days before and after the storm hit, laying bare the government's inability to respond to the most elemental needs. They also demonstrate how the Bush administration's obsessive focus on terrorist threats fatally undermined the government's ability to respond to natural disasters. The incompetent response to Hurricane Katrina is a wake-up call to all Americans, wherever they live, about how distressingly vunerable we remain" -- COVER.
Originally published in hardcover in 2006 by Times Books. --t.p. verso.
Keywords: Hurricane Katrina, 2005.; Disaster relief; Emergency management; Disaster relief